The last giant continental tortoise of Europe: A survivor in the Spanish Pleistocene site of Fonelas P-1 - Perez Garcia, Adan (2017)
The presence of remains of a giant tortoise in the lower Pleistocene site of Fonelas P-1 (Guadix Basin, Betic Ranges; Granada, southeastern Spain) is reported and analyzed herein for the first time. This finding represents the youngest evidence of a large tortoise in continental Europe, dating the age of extinction of this successful lineage as several hundred thousand years younger than previously thought. So far, the most recent record known for continental Europe was at least 400,000ï¿½years older than the occurrence reported herein (Vaterï¿½, Greece), that for the Spanish record being about 1.3ï¿½millionï¿½years older (Las Higueruelas). This finding is justified as the youngest evidence of Titanochelon, a genus recorded in Europe since the beginning of the Miocene, which includes the largest terrestrial turtles known for the entire European fossil record. The decrease in the biogeographical distribution area and the final extinction of these temperature-sensitive animals in Europe is here recognized as a result of the climate changes documented during the Pliocene and lower Pleistocene. The identification of taxa with environmental and ecological requirements as restrictive as those known for the extant and extinct large tortoises, living in continental Europe 2.0ï¿½Ma, has important consequences. Thus, although the paleoclimatic inferences generally assumed for the whole of Europe interpret cooler and drier conditions at the end of the Pliocene, by the increase of the seasonality and the beginning of the glacial activity in the Northern Hemisphere, the record of Fonelas P-1 indicates that, in southern Europe or, at least, in the endorheic basins of the Betic Ranges, warmer climatic conditions than in the rest of the continent continued being present in these chronologies of the lower Pleistocene, being favorable for the persistence of these large tortoises.